Анализ годового цикла радиолокационных наблюдений термиков в нижнем слое тропосферы - Олейников, В. Н.; Евсеев, Д. Б.; Юдин, С. В.; Гарячий, Д. А.; Литвин-Попович, А. И. (ХНУРЭ, 2011)
A results of an annual cycle of radar convective thermal heterogeneities observations in troposphere are discussed. Relation of number of these phenomena with meteoparameters is considered. It is shown that their number to the greatest degree depends on value of diurnal variation of temp
Keywords: явления радиолокационных отражений от ясного неба; зондирование атмосферы